Government consumption in the DINA framework: allocation methods and consequences for post-tax income inequality - Lukas Riedel; Holger Stichnoth (International Tax and Public Finance, 2024)
About half of government expenditure in the United States takes the form of government consumption (e.g., education, defense, infrastructure). In many studies of post-tax inequality based on the Dina framework (including the influential study by Piketty et al. (Q J Econ 133(2):553–609, 2018), government consumption is allocated either proportionally to post-tax disposable income or on a per-capita basis, and the level of inequality is fairly sensitive to this choice. This paper provides direct evidence on how public education spending (a substantial part of government consumption) is actually distributed. An allocation proportional to post-tax disposable income is clearly rejected, while a lump-sum allocation is found to provide a good approximation.
Keywords: D31; H41; H52; I24; 340; Inequality; Redistribution; Education; In-kind transfers